Speech and language pathology interventions in spasmodic dysphonia: A bibliometric study - Daza, Mary Luz; Pérez, Rosa Mª; Camargo, Maryluz (Revista de Investigación en Logopedia, 2017)
This study aimed to characterize the scientific production related to speech-language interventions in Spasmodic Dysphonia. To this goal, eight databases were consulted - the Clinical Key, Biomed Central, Directory of Open Access Journals, Science Direct, Pubmed, Scielo, Virtual Health Library and Ebsco Discovery Service; based on a search protocol with three filters defined by 1) Title and summary of papers, 2) Aspects related to speech therapy and 3) Papers that answered the research question. The initial search yielded a total of 2,332 papers, mostly found in the Science Direct database and published in English. Once the first filter was applied, a total of 55 papers were remained, with the second filter 22, and the third filter three. Of the latter, two reported treatment results through case studies, two did so by comparing one experimental group and a control group and one measured results in a group through the filling of questionnaires. As a conclusion, there is little evidence to identify speech-language interventions in people with spasmodic dysphonia, which requires more studies and more publication of treatment results.